Circulating immune landscape and immune signatures in spontaneous HIV controllers - Navas, Adriana; dos Santos, Jéssica C.; van Cranenbroek, Bram; Vadaq, Nadira; Groenendijk, Albert L.; Vos, Wilhelm A. J. W.; Blaauw, Marc J. T.; van Eekeren, Louise; Rokx, Casper; Stalenhoef, Janneke E.; Berrevoets, Marvin A. H.; Netea, Mihai G.; et al. (Frontiers in Immunology, 2025)
A subset of people with HIV, termed HIV controllers (HIC), maintain low viral loads without antiretroviral therapy. To identify the immune cell architecture of HIV control, we profiled peripheral blood from 54 HIC (including 21 elite controllers, EC) and 1,044 non-controllers (non-HIC) in the 2000HIV study (NCT03994835) using high-dimensional cytometry and confounder-adjusted regression analysis. Both HIC and EC exhibited distinct innate immune profiles compared to non-HIC, marked by reduced frequencies of CCR5+ NKT and TCRγδ1+ cells. EC further showed increased neutrophils and TCRγδ2+ cells, and reduced eosinophils. Unsupervised clustering revealed elevated CD11c and CD1c expression on TCRγδ2+ cells in EC, correlating with IFNγ production, suggesting a proinflammatory γδ T cell program unique to EC. Adaptive immune profiling showed shared features between HIC and EC: increased CD4+ naïve and Th1/17 cells, reduced Th17 and Tfh cells, and higher CD8+ TEMRA and Tc1/17 cells with reduced memory subsets. Both groups showed increased naïve and immature B cells and decreased switched memory and plasma cells. EC uniquely exhibited increased IgA+ memory B cells —a feature consistent with enhanced mucosal immunity— and decreased IgG+ memory B cells and CD307d expression, suggestive of mucosal imprinting and reduced exhaustion. Comparison of HIC and EC revealed divergent CCR5 and CXCR4 expression: EC had higher frequencies of CCR5+ and CXCR4+ CD4+ and CD8+ T cells. These elevations correlated with circulating chemokines, notably MIF for CXCR4, implying protective ligand occupancy. HIC instead showed overall lower co-receptor expression and ligand correlations. In conclusion, while HIC and EC share a core immune phenotype linked to viral control, EC-specific features— γδ T cell activation, IgA+ memory enrichment, and chemokine receptor regulation—may underlie more robust or distinct immune control mechanisms. This profiling resource offers new avenues for HIV cure-focused strategies.